The incidence of inflation : or who gets hurt? by Seymour E. Harris ; Protection against inflation, by H.S. Houthakker ; The share of wages and salaries in manufacturing incomes, 1947-56, by Alfred H. Conrad. Materials prepared in connection with the study of employment growth, and price levels for consideration by the Joint Economic Committee, Congress of the United States. Study papers nos. 7,8,and 9 - Harris, Seymour. E; Houthakker, H.S.; Conrad, Alfred.H; United States Congress Joint Economic Committee (Washington, DC : United States Government Printing Office, 1959)
The papers in this book submitted for the consideration of the members of the Joint Economic Committee and others are study paper 7, 8, and 9, "Incidence of Inflation: Or who gets hurt; Protection against inflation; and The share of wages and salaries in manufacturing incomes, 1947- 56.
rpm 01/06/2016
Loans
Keywords: Inflation (Finance) -- United States; Inflation (Finance); United States